The effect of patient education on maternal fasting blood glucose in gestational diabetes mellitus in randomized controlled trials: a systematic review and meta-analysis - Alissa Paudel; Regis C. Pearson; Elizabeth Mirsky; Alexandria Quesenberry Wilson; Alixandra Hunzicker; Kelsey L. Grabeel; Justin Thorne; Jill M. Maples (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective To evaluate the effect of patient education interventions on fasting blood glucose (FBG) in patients with gestational diabetes mellitus (GDM).Methods Electronic search of MEDLINE/PubMed, CINAHL (EBSCO), Embase (Elsevier), Cochrane Central Register of Controlled Trials (CENTRAL), and Clinicaltrials.gov was conducted from inception to September 16, 2022. Randomized controlled trials which evaluated the effect of GDM-specific education on biochemical assessment of FBG during pregnancy or within 6 weeks postpartum in patients with GDM were included. Meta-analysis was performed of studies reporting FBG using a fixed effects model to determine mean blood glucose difference and corresponding 95% confidence intervals. Cochrane risk of bias tool was used to assess study quality.Results Fourteen randomized controlled trials enrolling 1885 patients were included. A total of 8 studies with 893 participants were eligible for inclusion in the meta-analysis. The mean effect size was significant: Cohen’s d = −0.53 (95% CI [-0.67, −0.34], z = −7.36; p < 0.001). The overall risk of bias for included studies was low.Conclusion A GDM-specific education intervention resulted in improved glucose control during pregnancy and up to 6 weeks postpartum. Due to the number of studies a moderator analysis could not be conducted to determine the most effective educational intervention strategies. More studies are needed to determine efficacious interventions that are cost-effective and can be broadly implemented throughout health systems.